Randomised controlled trial of joint crisis plans to reduce compulsory treatment for people with psychosis: economic outcomes. - Barbara Barrett (Public Library of Science (PLoS), 2013)
Background Compulsory admission to psychiatric hospitals may be distressing, disruptive to patients and families, and associated with considerable cost to the health service. Improved patient experience and cost reductions could be realised by providing cost-effective crisis planning services. Methods Economic evaluation within a multi-centre randomised controlled trial comparing Joint Crisis Plans (JCP) plus treatment as usual (TAU) to TAU alone for patients aged over 16, with at least one psychiatric hospital admission in the previous two years and on the Enhanced Care Programme Approach register. JCPs, containing the patient's treatment preferences for any future psychiatric emergency, are a form of crisis intervention that aim to mitigate the negative consequences of relapse, including hospital admission and use of coercion. Data were collected at baseline and 18-months after randomisation. The primary outcome was admission to hospital under the Mental Health Act. The economic evaluation took a service perspective (health, social care and criminal justice services) and a societal perspective (additionally including criminal activity and productivity losses). Findings The addition of JCPs to TAU had no significant effect on compulsory admissions or total societal cost per participant over 18-months follow-up. From the service cost perspective, however, evidence suggests a higher probability (80%) of JCPs being the more cost-effective option. Exploration by ethnic group highlights distinct patterns of costs and effects. Whilst the evidence does not support the cost-effectiveness of JCPs for White or Asian ethnic groups, there is at least a 90% probability of the JCP intervention being the more cost-effective option in the Black ethnic group. Interpretation The results by ethnic group are sufficiently striking to warrant further investigation into the potential for patient gain from JCPs among black patient groups. Trial registration Current Controlled Trials ISRCTN11501328.